Islamic Anthropology, Based on Key Passages in the Qur’an - Sejdini, Zekirija (Mimetic theory and Islam, 2019)
The chapter delineates some of the main features of Islamic anthropology, based upon key Quranic passages. The complexity of such a survey is acknowledged: apparent contradictions appear because of the differing contexts and topics of the verses considered. The picture which emerges is of a humanity which is endowed by God with a special dignity in creation, as emphasized in the second sura. Man is appointed as governor or representative of God on earth. Among the deficiencies of human beings which hinder this task, envy is identified as the source of other moral weaknesses. Envy is accredited to an inordinate love of mortal things when the individual has strayed from God. Belief in the resurrection and an afterlife is important for countering this as well as a clear understanding of the nature of property rights in Islamic thought (absolute property versus entrusted goods). The spiritual journey of the soul is understood as a growth of awareness and self-criticism towards the highest stage of perfection, the ‘calm and contented soul’.